Esophageal foreign body removal using endoscopy in cat - Sitaria Fransiska Siallagan; Herawati Napitu; Arni Diana Fitri; Nindya Dwi Utami; Soenarti D. Waspada; Deni Noviana (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
A 10-months-old cross long hair cat named Casper with clinical symptom of vomiting mixed with slimy cat feed was referred to Veterinary Teaching Hospital, Faculty of Veterinary Medicine, Bogor Agricultural University to endoscopy examination and therapy. The owner believed that Casper ate a 5 cm long sewing needle a few days earlier. The history and physical examination were examined at DNA Clinic with symptoms of lack of appetite and becoming quieter and calmer. Radiogram showed the needle was in thorax area with a vertical needle penetrating the esophageal wall. Removal of the needle and observation of the esophagus area were done using endoscopy under general anesthesia. Using endoscopy, it was known that the needle was swallowed along with the sewing thread with position of all needles penetrating the esophagus wall and leaving a small amount of thread on the lumen. The needle was pulled back to the esophageal lumen by pulling the remaining thread and then both needle and the thread were pulled back out using an alligator grasping forceps that used through working channel. Therapy given after endoscopy was antibiotics and anti-emetics.